Momento fletor resistente à flambagem lateral com torção de vigascelulares de aço em temperatura ambiente e situação de incêndio - Caroline Corrêa de Faria (2019)
This work deals with a numerical study on the structural behavior of steel cellular beams at room temperature, and under fire condition, focused on the lateral-torsional buckling limit state. The main objective is to propose new design procedures for lateral-torsional buckling of steel cellular beams. To this end, a finite element model was developed and validated by comparison against experimental results available in literature, and, subsequently, used in a parametric study of steel cellular beams deriving from hot rolled I sections made in Brazil. Based on the results of the parametric study, it was proposed the lateral-torsional buckling resistance was calculated by multiplying the plastic moment by new reduction factors for the lateral-torsional buckling, which were obtained through regression of the numerical buckling curves. The proposed procedures were verified against 1535 numerical models at room temperature, and against 10771 numerical models under fire conditions, presenting better accuracy than those available in literature.